Measurement of the single-spin asymmetry Ay0 in quasi-elastic 3He↑(e,e′n) scattering at 0.4 < Q2 < 1.0 GeV/c2 - E. Long (Physics Letters B, 2019)
Due to the lack of free neutron targets, studies of the structure of the neutron are typically made by scattering electrons from either 2H or 3He targets. In order to extract useful neutron information from a 3He target, one must understand how the neutron in a 3He system differs from a free neutron by taking into account nuclear effects such as final state interactions and meson exchange currents. The target single spin asymmetry Ay0 is an ideal probe of such effects, as any deviation from zero indicates effects beyond plane wave impulse approximation. New measurements of the target single spin asymmetry Ay0 at Q2 of 0.46 and 0.96 (GeV/c)2 were made at Jefferson Lab using the quasi-elastic He↑3(e,e′n) reaction. Our measured asymmetry decreases rapidly, from >20% at Q2=0.46 (GeV/c)2 to nearly zero at Q2=0.96 (GeV/c)2, demonstrating the fall-off of the reaction mechanism effects as Q2 increases. We also observed a small ϵ-dependent increase in Ay0 compared to previous measurements, particularly at moderate Q2. This indicates that upcoming high Q2 measurements from the Jefferson Lab 12 GeV program can cleanly probe neutron structure from polarized 3He using plane wave impulse approximation. Keywords: Neutron, Quasi-elastic, Polarized, 3He, Electron scattering, Single spin asymmetry